Functional Role of Neural Injury in Obstructive Sleep Apnea - Saboisky, Julian P.; Butler, Jane E.; Gandevia, Simon C.; Eckert, Danny J. (Frontiers in Neurology, 2012)
The causes of obstructive sleep apnea (OSA) are multifactorial. Neural injury affecting the upper airway muscles due to repetitive exposure to intermittent hypoxia and/or mechanical strain resulting from snoring and recurrent upper airway closure have been proposed to contribute to OSA disease progression. Multiple studies have demonstrated altered sensory and motor function in patients with OSA using a variety of neurophysiological and histological approaches. However, the extent to which the alterations contribute to impairments in upper airway muscle function, and thus OSA disease progression, remains uncertain. This brief review, primarily focused on data in humans, summarises: 1) the evidence for upper airway sensorimotor injury in OSA and 2) current understanding of how these changes affect upper airway function and their potential to change OSA progression. Some unresolved questions including possible treatment targets are noted.